2013
DOI: 10.4067/s0717-95022013000200026
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Nicotine on the Incisive Teeth and Expression of Vimentin in Rats

Abstract: FARUK. E. R.; DEVECI, E.; KALKANLI, S. & DEVECI, B.The effects of nicotine on the incisive teeth and expression of vimentin in rats. Int. J. Morphol., 31(2):516-519, 2013. SUMMARY:Nicotine is an alkaloid toxic effects of oral cavity. In this study,14 adult Sprague-Dawley rats weighing 230-260 mg (±10 mg) were used as experimental animal. The rats of experimental group (n=6) were nicotinized systemically with nicotine sulphate, 2mg/kg subcutaneously, daily in period of 28 days. Pulp, alveolar bone tissue, perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In addition, the action of nicotine and lipopolysaccharide on SIRT1 mRNA up-regulation in hGFs has an anti-inflammatory and pro-inflammatory effect 33 . Studies show that nicotine may alter periodontal cells directly via nAChRs, leading to pathophysiological effects and the development of tobacco-related diseases in these cells 34-36 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the action of nicotine and lipopolysaccharide on SIRT1 mRNA up-regulation in hGFs has an anti-inflammatory and pro-inflammatory effect 33 . Studies show that nicotine may alter periodontal cells directly via nAChRs, leading to pathophysiological effects and the development of tobacco-related diseases in these cells 34-36 .…”
Section: Resultsmentioning
confidence: 99%
“…Cigarette smoke condensate has been reported to up-regulate MMP-1, MMP-8 and MMP-9 gene expression in vascular endothelial cells [34]. Er et al [13] found that fibroblast metabolism could be altered by nicotine action and intercellular matrix synthesis was affected. It also affects periodontal ligament fibroblasts and stimulates osteoclasts activity [19,42].…”
Section: Discussionmentioning
confidence: 99%